Advances in the treatment of transthyretin amyloidosis - Intissar Anan (eGastroenterology)
This review aims to provide a comprehensive overview of the existing therapeutic options for managing neuropathic and/or cardiac manifestations associated with transthyretin amyloidosis (ATTR), along with investigational therapeutic candidates under evaluation in ongoing clinical trials. Additionally, emerging approaches for combating this life-threatening disease are discussed. Recent advancements in non-invasive diagnostic techniques for the detection of ATTR have facilitated improved diagnosis and identification at an earlier disease stage, thereby enhancing the potential efficacy of therapeutic interventions. Presently, there exists a range of clinically available treatments targeting ATTR, alongside investigational agents undergoing assessment in clinical trials. Therapeutic modalities encompass tetramer stabilisation, gene silencing, and ATTR fibril disruption and removal strategies. Historically, ATTR has been underdiagnosed. However, with the progression of diagnostic methodologies and the introduction of disease-modifying treatments, early diagnosis and initiation of treatment have significantly transformed the management of this condition, and effective treatment modalities have been introduced and are under development.